Oxygen Desaturation Complicates Feeding in Infants With Bronchopulmonary Dysplasia After Discharge - Singer, Lynn (1992)
Recurrent episodes of hypoxemia may affect the growth, cardiac function, neurologic outcome, and survival of infants with bronchopulmonary dysplasia (BPD). As oral feeding might stress these infants by compromising pulmonary function even after hospital discharge, we measured oxygen saturation (Sao(2)) via pulse oximetry before, during the initial 10 minutes of, and immediately after oral feeding in 11 patients with BPD, 12 very low birth weight infants, and 23 healthy full-term infants. All infants with BPD had been previously discharged from the hospital after weaning from supplemental oxygen. Studies were done at a mean postconceptional age of 43 weeks while the infants were fed at home by one of their parents. Levels of Sao(2) for the three groups were comparable before and during feeds. After feeding, the infants with BPD had significantly lower mean levels of Sao(2) (84 ± 8% [SD] vs 93 ± 4% and 93 ± 3%, respectively; P < .01). They also spent more time after feeding with an Sao(2) <90% (64 ± 34% of time vs 27 ± 33% for the very low birth weight and 22 ± 20% for the term group; P < .01) and greater time with an Sao(2) <80% (37 ± 28% vs 4 ± 10% and 4 ± 8%, respectively; P < .01). Desaturation in infants with BPD was related to larger volume and faster oral intake during feeding. Thus, the data indicate that desaturation after feeding remains a recurrent problem for survivors of BPD after discharge. Individual approaches which incorporate parental education and behavioral interventions might decrease the risk of significant hypoxemia during oral feeding in infants with BPD.